2002
DOI: 10.1097/00008571-200201000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Implications of circadian gene expression in kidney, liver and the effects of fasting on pharmacogenomic studies

Abstract: Pharmacogenomics offers the potential to define metabolic pathways and to provide increased knowledge of drug actions. We studied relative levels of gene expression in the rat using a microarray with 8448 rat UniGenes (1928 known genes, 6520 unknown ESTs) in the liver and kidney as a function of time of day and then of feeding regime, which are common variables in preclinical pharmacogenomic studies. We identified 597 genes, including several key metabolic pathways, whose relative expression levels are signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
83
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(91 citation statements)
references
References 44 publications
8
83
0
Order By: Relevance
“…Interestingly, fasting alters circadian gene expression in various tissues. 43) Also, streptozotocin-induced diabetic rat showed phase shift and/or upswing of clock genes expressions. 12) Therefore, plasma level of insulin and glucose may be the candidates of modulator of circadian gene expression in adipose tissue.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, fasting alters circadian gene expression in various tissues. 43) Also, streptozotocin-induced diabetic rat showed phase shift and/or upswing of clock genes expressions. 12) Therefore, plasma level of insulin and glucose may be the candidates of modulator of circadian gene expression in adipose tissue.…”
Section: Discussionmentioning
confidence: 98%
“…Each study has employed a different plat form, data analysis methods, and screened different numbers of genes. In general, it appears that about 10 % of the genes are circadianly expressed in the liver, heart, and kidneys (Akhtar et al, 2002;Kita et al, 2002;Panda et al, 2002;Storch et al, 2002;Ueda et al, 2002). Interestingly, in the fibroblasts it has been reported that fewer than 100 genes (or about 2% of the genes present in these cells) are rhythmically expressed (Duffield et al, 2002;Grundschober et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In the recent years, the DNA microarray technique has been successfully used to study circadian gene expression in the SCN, liver, heart, kidney, and fibroblasts (Grundschober et al, 2001;Akhtar et al, 2002;Duffield et al, 2002;Kita et al, 2002;Panda et al, 2002;Storch et al, 2002;Ueda et al, 2002). The picture that is emerging from these studies indicates that in each tissue or organ a certain number of genes (approximately 2-10 %) are under circadian control.…”
Section: Introductionmentioning
confidence: 99%
“…For example, E box enhancer regulates gene expression of a variety of factors that include a neuropeptide arginine vasopressin (Jin et al , 1999), a secreted protein prokineticin 2 (Cheng et al , 2002), a serine protease inhibitor plasminogen activator inhibitor-1 (Maemura et al , 2000), a transcription factor c-Myc (Fu et al , 2002), and the Cdc2 kinase WEE1 . Recent studies using DNA microarray technology identified a large number of rhythmically expressed genes (Grundschober et al , 2001;Akhtar et al , 2002;Duffield et al , 2002;Humphries et al , 2002;Kita et al , 2002;Panda et al , 2002a;Storch et al , 2002;Ueda et al , 2002;Oishi et al , 2003). Some of these genes may be regulated directly by the transcription factors involved in the oscillatory loops through the upstream ciselements, such as E box, REV-ERB α /ROR response element, and DBP-binding site (Ueda et al , 2002).…”
Section: Oscillation Of Mammalian Circadian Clockmentioning
confidence: 99%